'Aerial Silk Roads': Airport Infrastructures in China's Belt and Road Initiative. Issue 4 (7th July 2020) - Lin, Weiqiang; Ai, Qi
ABSTRACT: The Belt and Road Initiative (BRI) is widely touted as China's answer to development through international connectivity. The scheme has often been linked to China's objectives of crafting a new world order centred on itself and/or stabilizing its economy through externalizing surplus capacity. While important in broadly framing China's relationship with the world, this article posits that such a fixation on state‐centric visions of development leaves the door open for misinterpretation, mistaking the BRI for a coherent set of projects imposed 'from above'. Delving into the execution of infrastructure planning on the ground, this article argues that taking a practice‐oriented approach to large‐scale developmental schemes can more accurately shed light on their internally fractured processes. Two airport projects in central China branded as part of the country's 'aerial Silk Roads' are examined to illustrate these dynamics, with particular attention paid to the airports' shifting conceptualizations, the competitive motivations behind their (re)construction, and the social relations sustaining them. The authors argue that closely tracking the unfolding of a range of infrastructure planning practices within specific projects can demystify modern‐day developmental programmes like the BRI, by revealing how their 'grand' visions are often reinterpreted, altered and frustrated at local levels, even before they have a chance to influence the world.